Tall fescue cultivar and fungal endophyte combinations influence plant growth and root exudate composition - Guo, Jingqi; McCulley, Rebecca L.; McNear, David H. (Frontiers in Plant Science, 2015)
Tall fescue (Lolium arundinaceum (Schreb.)) is a cool-season perennial grass used in pastures throughout the Southeastern United States. The grass can harbor a shoot-specific fungal endophyte (Epichloë coenophiala) thought to provide the plant with enhanced resistance to biotic and abiotic stresses. Because alkaloids produced by the common variety of the endophyte cause severe animal health issues, focus has been on replacing the common-toxic strain with novel varieties that do not produce the mammal-toxic alkaloids but maintain abiotic and biotic stress tolerance benefits. Little attention has been given to the influence of the plant-fungal symbiosis on rhizosphere processes. Therefore, our objective was to study the influence of this relationship on plant biomass production and root exudate composition in tall fescue cultivars PDF and 97TF1, which were either not infected with the endophyte (E-), infected with the common toxic endophyte (CTE+) strain or with one of two novel endophytes (AR542E+, AR584E+). Plants were grown sterile for three weeks after which plant biomass, total organic carbon, total phenolic content and detailed chemical composition of root exudates were determined. Plant biomass production and exudate phenolic and organic carbon content were influenced by endophyte status, tall fescue cultivar, and their interaction. GC-TOF MS identified 132 compounds, including lipids, carbohydrates and carboxylic acids. Cluster analysis showed that the interaction between endophyte and cultivar resulted in unique exudate profiles. This is the first detailed study to assess how endophyte infection, notably with novel endophytes, and tall fescue cultivar interact to influence root exudate composition. Our results illustrate that tall fescue cultivar and endophyte status can influence plant growth and root exudate composition, which may help explain the observed influence of this symbiosis on rhizosphere biogeochemical processes.